REVIEW ARTICLE DUKUNGAN KELUARGA MENINGKATKAN KUALITAS HIDUP LANSIA - MAY DWI YURI SANTOSO (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
Family support is included in supporting factors (supporting factors) that can affect a person's life and lifestyle which improves the health status and quality of life of the elderly. The purpose of this literature is to review various literature on families about landscape quality that can be used as information data to make the lives of the elderly more meaningful and inadequate with the lives they live each, questioning the benefits of living by supporting the family. The method used is a scientific electronic bibliographic database of articles published through Google Scholar as many as 1,370,000 articles, Pubmed as many as 9,376 articles, Microsoft Academic 60 articles and from Google Scholar as many as 655 articles, then 10 articles were selected. The results of a review of 10 selected articles agreed to family support to improve the quality of the elderly. The family has a very important role in the concept of a healthy family that has an elderly, where the family is a support system that provides direct care to family members who are experiencing physical, psychological, social and environmental difficulties that will support the improvement of the quality of life of the elderly.